Penerapan Hukum Syariah dalam Aktivitas Perdagangan: Perspektif Ekonomi Islam Kontemporer - Zulpan Kurniawan; Ahmad Muflih Makarim; Sri Handayani (Universitas Serambi Mekkah, 2025)
Trade is an economic activity that continues to evolve in line with the dynamics of the times. In the context of Muslim society, the implementation of Sharia law in trading practices becomes crucial to ensure that every transaction aligns with Islamic principles. This article aims to examine how the principles of Sharia law are applied in contemporary trade activities, including in digital spaces such as e-commerce. Using a literature review approach, this study explores recent literature on the topic. The findings indicate that the principles of justice, honesty, prohibition of usury, and transparency remain the fundamental pillars in Sharia trade practices. On the other hand, challenges such as a lack of Sharia literacy, suboptimal regulations, and the dominance of conventional systems continue to be major obstacles in its implementation. Nevertheless, the potential for the development of Sharia-compliant trade remains vast, especially with the right education, digital tools, and support from the government and Islamic financial institutions.